Agonism of Histaminergic-H1 Receptors in Ischemic Postconditioning During Cerebral Ischemia-Reperfusion Injury is Protective - Singh, Prabhat; Sharma, Bhupesh (Current Neurovascular Research, 2020)
Background: Stroke is associated with cerebral ischemia/reperfusion (I/R) injury. Ischemic postconditioning (IPoC) reduces cerebral ischemic injury in rats and offers neuroprotection. The central histaminergic pathway possesses a crucial role in the pathogenesis of cerebral I/R, but its neuroprotective role in IPoC is still unidentified. Objective: This research explored the role of the histaminergic in IPoC during cerebral I/R injury in the rat. Methods: Global cerebral ischemia/reperfusion (GCI/R) injury in Wistar albino rats was induced by occluding the bilateral carotid arteries for 10 minutes, followed by reperfusion. IPoC was provided by giving three episodes of I/R post GCI (10 min), after which of reperfusion was permitted. Inclined- beam-walk, hanging-wire, lateral-push, and rota-rod tests were employed to assess motor functions, and Morris water maze (MWM) was used to assess spatial learning as well as memory in animals. Cerebral oxidative markers (thiobarbituric acid reactive species-TBARS, reduced glutathione- GSH), inflammatory markers (myeloperoxidase-MPO), acetylcholinesterase activity- AChE, infarct size, and histopathological changes were also assessed. L-histidine and chlorpheniramine were used as histaminergic agonists and antagonists. Results: I/R animals showed a reduction in memory and motor function, and an increase in cerebral oxidative stress, inflammation, AChE activity, infarct size and histopathological changes. Episodes of IPoC post-ischemia attenuated the deleterious effects of I/R injury. Pretreatment (30 min before cerebral ischemia) with L-histidine mimicked the neuroprotective effects of IPoC. However, neuroprotection produced by IPoC was abolished by pretreatment with chlorpheniramine (histaminergic- H1 receptor antagonist). Conclusion: IPoC may provide neuroprotection against cerebral I/R induced brain injury by modulating the histaminergic-H1-receptor pathway.
Keywords: brain injury